Using a Connected Learning Framework to Promote Democratic Education During a Transition to Online Learning - Abigail H Baker; Jennifer L Kassimer (Middle Grades Review, 2021)
In this essay, we discuss how a Connected Learning (CL) approach to education can offer students and teachers a democratic framework to follow when designing instruction, especially with the recent shift to online and hybrid instruction due to the global pandemic. We present literature on the opportunities and challenges of transitioning to online instruction in the midst of the pandemic. We then discuss how the CL framework promotes a democratic approach to teaching and learning. Finally, we offer guidance on how to design a unit or lesson plan using a CL framework to provide both a connected and democratic learning experience for students. We also offer suggestions on how to foster an innovative, authentic learning experience that includes elements of an online or hybrid context to support connected learning. Drawing on a classroom example from the field, we conclude with recommendations for utilizing non-traditional, formative assessments to fairly assess a range of learning outcomes as demonstrated by students.
Keywords: Democratic Education; Connected Learning Theory; Connected Learning Framework; Online Instruction; Formative Assessment